Acrylate polymer coated side-polished fiber with graphene oxide nanoparticles for ultrafast fiber laser operation - Ahmad, Harith; Zulkifli, Ahmad Zarif; Tiu, Zian Cheak (IOP Publishing, 2018)
In this work, a mode-locked fiber laser with a side-polished fiber coated with graphene oxide nanoparticles as a saturable absorber (SA) is proposed and demonstrated. The SA is further coated with an acrylate polymer layer to add strength and durability, thus enabling real-world applications to be realized. The coated SA is capable of generated a pulsed output with a pulse width, pulse energy and pulse peak power of 1.09 ps, 0.013 nJ and 0.012 kW respectively. The cavity has a threshold power of 131.7 mW, and the output signals have a constant signal-to-noise ratio of about 33 dB over a test period of 1 h, indicating a highly stable output. The protective polymer coating allows a simple way to manufacture a rugged device with no penalty to performance.